A guide to upcoming policy changes 2019: What's in store. Issue 17 (19th August 2019) - Crown, Hannah
Abstract : A swathe of new big policy documents are hitting the early years sector from September, starting with the new inspection framework. Hannah Crown has a handy summary of what is happening and when